Pharmacokinetic and pharmacogenetic associations with dolutegravir neuropsychiatric adverse events in an African population. (29th August 2022) - Griesel, Rulan; Sinxadi, Phumla; Kawuma, Aida; Joska, John; Sokhela, Simiso; Akpomiemie, Godspower; Venter, Francois; Denti, Paolo; Haas, David W; Maartens, Gary
Abstract: Background: Dolutegravir has been associated with neuropsychiatric adverse events (NPAEs), but relationships between dolutegravir concentrations and NPAEs are unclear. Objectives: To determine in an African population whether a concentration–response relationship exists between dolutegravir and treatment-emergent NPAEs, and whether selected loss-of-function polymorphisms in genes encoding UDP-glucuronosyltransferase-1A1 (the major metabolizing enzyme for dolutegravir) and organic cation transporter-2 (involved in neurotransmitter transport and inhibited by dolutegravir) are associated with NPAEs. Methods: Antiretroviral therapy-naive participants randomized to dolutegravir-based therapy in the ADVANCE study were enrolled into a pharmacokinetic sub-study. Primary outcome was change in mental health screening [modified mini screen (MMS)] and sleep quality from baseline to weeks 4, 12 and 24. Dolutegravir exposure was estimated using a population pharmacokinetic model. Polymorphisms analysed were UGT1A1 rs887829 and SLC22A2 rs316019. Results: Data from 464 participants were available for pharmacokinetic analyses and 301 for genetic analyses. By multivariable linear regression, higher dolutegravir exposure was associated with worsening sleep quality only at week 12 [coefficient = −0.854 (95% CI −1.703 to −0.005), P = 0.049], but with improved MMS score at weeks 12 and 24 [coefficient = −1.255 (95% CI −2.250 to −0.261), P = 0.013 and coefficient = −1.199 (95% CI −2.030 to −0.368), P = 0.005, respectively]. The UGT1A1 and SLC22A2 polymorphisms were not associated with change in MMS score or sleep quality. Conclusions: Only at week 12 did we find evidence of a relationship between dolutegravir exposure and worsening sleep quality. However, higher dolutegravir exposure was associated with improved MMS scores, suggesting a possible beneficial effect.